Tidal evolution in the Ria de Aveiro: astronomical and meteorological components - Fradinho, Dulce Maria Chuvas Gordinho Maia (2017)
Ria de Aveiro is a shallow lagoon, located in the Northwest of Portugal, separated from the sea by a barrier island, with which is connected through an artificial channel fixed by breakwaters. This work aims to study the tidal changes induce by geomorphologic modifications occurred in Ria de Aveiro between 1987/88 and 2017, analysing the variations on the tidal amplitude and phase of tidal constituents: 2, 2, 4, 6 and . This work also aims to determine the frequency of storm surge phenomena occurrence, between 2012 and 2017, determining which factors influence the generation of the storm - variation in atmospheric pressure, intensity and direction of the wind and precipitation - and verify the increase of the water level in Ria de Aveiro caused by these meteorological events. Data were collected on tidal gauges in the main channels of the lagoon. Annual amplitude and phase variation graphics of tidal constituents: 2, 2, 4, 6 and (which were computed using the T-Tide Matlab package), were drawn for the different years. This allowed to observe the annual tidal evolution and to verify if there had been any relevant changes during the time interval in which the data collection took place. Annual series of the residual meteorological tide were determined for each year between 2012 and 2017, by subtracting the astronomical predicted tides from the measured tidal signal, and to identify the distribution of the positive and negative anomalies in each station studied, and find the relationship between meteorological variables and the generation of tidal elevations. For this purpose, were drawn graphs of the atmospheric pressure, wind intensity and direction, precipitation and water level and residual graphs. From the results obtained, in general and for each station, the annual amplitude values are increasing while the phase is decreasing. Between 1987/88 and 2002/03 there was an increase in amplitude in the studied stations. This change is a consequence of the increase in the depth of the navigation channels due to dredging operations in 1998. From 2012 to 2017 and after the North breakwater extension there are no significant variations in tidal amplitude or phase. Thus, the extension of the North breakwater did not produce appreciable changes in the tidal dynamics in Ria de Aveiro. By the analysis of the meteorological tide was verified that positive anomalies are more frequent than negative. From the different events occurring between 2012 and 2017, only two positive storm surges influenced the entire lagoon, having been generated by adverse meteorological conditions verified at national level. The remaining were manifested only locally. The events with negative anomalies occurred in a smaller number. From the analysis of all the studied events, it was verified that the higher values of the level of the sea water did not result from the existence of meteorological tides, but from the spring tides. Therefore, the joining of a positive storm event at high tide of spring tides will constitute a high risk for the marginal areas of the lagoon, which may be flooded.